2017
DOI: 10.21767/2572-5610.10017
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenic and Haematological effects of Aqueous and Ethanolic Extracts of Hymenocardia acida Stem Bark on Aluminium-Induced Toxicity in Male Wistar Rats

Abstract: This study was designed to determine the spermatogenic and haematological effects of aqueous and ethanolic stem bark extracts of Hymenocardia acida on Aluminium chloride-induced toxicity in male wistar rats. Thirty male albino Wistar rats were used and toxicity was induced using 100 mg/kg body weight (bw) AlCl 3 . The rats were distributed into six groups of five rats each. The drug and extract administration lasted for seven days, thereafter the animals sacrificed. The results indicated that oral dose of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The reduction of RBC, HGB by AlCl 3 in this study suggests the induction of anemia. Also, hematological results indicated that AlCl 3 led to a significantly increased WBC when compared to SCO, D-gala, and control groups (Yakubu et al, 2017). Increase in WBC is suggestive of leukocytosis and anemia as seen from the corresponding decreases in RBC which may indicate the activation of the immune system to form defensive cells (Adedosu et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The reduction of RBC, HGB by AlCl 3 in this study suggests the induction of anemia. Also, hematological results indicated that AlCl 3 led to a significantly increased WBC when compared to SCO, D-gala, and control groups (Yakubu et al, 2017). Increase in WBC is suggestive of leukocytosis and anemia as seen from the corresponding decreases in RBC which may indicate the activation of the immune system to form defensive cells (Adedosu et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…This decrease in FSH may be due to C. pentandra toxic effect on the anterior pituitary gland, causing oxidative damage to the anterior pituitary gland's architecture, responsible for the generation of FSH (glycoprotein hormone) and luteinizing hormone. The decline in testosterone levels in groups administered with aqueous leaf extracts of C. pentandra suggested that its phytochemical composition may reduce the effect of the pituitary gland and testosterone synthesis [19] The effect of aqueous leaf extract of C. pentandra on oxidative stress of testosterone propionate-induced benign prostatic hyperplasia in male rats had a non-significant increase (p > 0.05) in Lactate Dehydrogenase (LDH) activity in Groups 3 to 6 compared to the positive and negative control. Superoxide Dismutase (SOD) concentration in Groups 3 to 6 was significantly decreased (p > 0.05) compared to negative and positive control.…”
Section: Discussionmentioning
confidence: 99%